PERFORMANCE OF PEOPLE'S BUSINESS CREDIT - Titin RULIANA; Eddy SOEGIARTO K; Rita Lisu LOTTONG (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
People’s Business Credit program launched by the government of the Republic of Indonesia aims to accelerate the development of primary sectors and the empowerment of small-scale enterprises, to improve accessibility to credit and institutions financial, reducing poverty and expanding employment opportunities. Every year the People's Business Credit (it's called as KUR) disbursed by the government is constantly increasing. This study aimed to analyze: (1) Decrease in performance of people's business credit at PT. Bank Rakyat Indonesia (Persero) Tbk, Branch of Samarinda, Unit of Sungai Pinang Dalam from year 2012 to 2014 when measured by Loan To Equity, Credit Risk Ratio, and Provission for Losses; (2) The cause of a decrease in performance of people's business credit at PT. Bank Rakyat Indonesia (Persero) Tbk, Branch of Samarinda, Unit of Sungai Pinang Dalam from year 2012 until 2014. The results showed that the performance of business credit at PT. Bank Rakyat Indonesia (Persero) Tbk, Branch of Samarinda, Unit of Sungai Pinang Dalam from year 2012 to 2014 has decreased measured from the Loan To Equity, Credit Risk Ratio and Provission for Loan Losses. The decline in the performance of the business credit is due to the non-performing loans / bad credit. The cause of problem loans, originated from the two parties namely: (a) Banking sector need to maximize the credit analysis of customers' predictions. (b) The customer, that is the element of intent to delay or do not pay their obligations to the Bank, and there is an element inadvertently means that the debtor is willing to pay but is unable / their business Bankrupt.